SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA PENERIMA BEASISWA DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DI SMA NEGERI 1 SIBERUT BARAT - Merici Tasibeddei; Ade Pratama; Heri Mulyono (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Decision Support System (DSS) is a computer-based system that helps in the decision-making process. Scholarships are a form of appreciation in the form of financial assistance given to individuals or organizations for work achievements that have been produced. Simple Additive Weighting (SAW) is one of the methods used in the decision-making process with weighted addition. The purpose of this study is that researchers will design a Decision Support System (DSS) to select prospective scholarship recipients by implementing the Simple Additive Weighting (SAW) method. This method was chosen because this method is able to carry out a ranking process which is continued with a weighting process for each attribute, so that it can select the best alternative from a number of alternatives (students) based on certain criteria and weights. The research on the Decision Support System for Selecting Scholarship Recipients Using the Simple Additive Weighting (SAW) Method at SMA Negeri 1 Siberut Barat was conducted using the Software Development Life Cycle (SDLC) method with the waterfall model. The waterfall model consists of five stages, namely analysis, design, implementation, testing, and maintenance. The tests used in this study were Alpha testing and Beta testing. The Decision Support System for Selecting Scholarship Recipients Using the Simple Additive Weighting (SAW) Method at SMA Negeri 1 Siberut Barat was developed using the Laravel11 framework with the PHP programming language and MYSQL database. Based on the results of the Alpha test (black box and white box testing) it can be concluded that all test results are good and the Alpha test is successful. Furthermore, based on the results of the beta test on the validation of expert staff, the percentage of the value obtained was 77.5% with the statement agree and the average value of the user questionnaire assessment was 85.63% with the statement strongly agree. Based on the results of the research and testing above, it can be described that the decision support system for selecting scholarship recipients using the simple additive weighting method at SMA Negeri 1 Siberut Barat which was designed is a functional requirement that is expected to facilitate officers in managing student data.